Analysis of influencing factors on displacement sampling performance of deep-sea gas-tight sampler - Fang, Yuanli; Chen, Daohua; Deng, Yinan; Huang, Haocai (Frontiers in Marine Science, 2022)
The collection and research of deep sea water has always been a hot and key topic in the field of marine research. Collecting seawater samples that can truly reflect the in-situ water composition information through a deep-sea sampler is an important technical means in the field of deep-sea exploration. The deep-sea water sampler designed in this subject samples deep-sea water by displacement sampling. According to the jet theory, the method of numerical calculation combined with experiment is adopted, the influence of indirect displacement, shape and diameter of sampling inlet, Coanda distance, sampling rate and other factors on the displacement effect is analyzed in this paper. The results of the study demonstrate that at low speed, multiple displacements can improve the displacement effect. In the high-speed sampling state, a single displacement method should be adopted. The design of making the sampling port as close as possible to the wall of the sampling cavity helps to strengthen the plane jet to improve the displacement efficiency. The displacement efficiency can be slightly improved by using the rectangular sampling inlet and outlet. As the extraction speed increases, the liquid mixing area becomes larger. Through discussion and comparison with similar research at home and abroad, the sampler has good performance and high sampling purity. The analysis of the effect of changes in sample temperature on the sampling displacement efficiency will be performed in the future. The research on the thermal insulation performance of the sampling channel will be put on the agenda.